2018
DOI: 10.1590/s1983-41952018000500005
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced concrete ribbed slabs with wide-beam

Abstract: Ribbed slabs have been widely used in buildings due to their many advantages, especially the decrease of concrete below the neutral line. This paper presents an experimental and computational study on ribbed slabs with wide-beam, two one-way slabs and two two-way slabs, with variable depths were tested to evaluate their resistance to punching and shear strength of slabs. Experimental and computational results showed that the wide-beam ribs connection is a critical point in the design of the slabs due to the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…Experimental studies such as those by Al-Bayati et al [1], [2], Arunkumar et al [3] and Sacramento et al [4] showed that the reduction of the solid area in waffle flat slabs can reduce their ultimate strength, leading to the punching shear cone extending beyond the solid area. There is a rule of thumb among designers to use the length of the solid area to be at least equal to 15% of the clear span between columns, but there is no scientific basis for this rule.…”
Section: Justificationmentioning
confidence: 99%
See 1 more Smart Citation
“…Experimental studies such as those by Al-Bayati et al [1], [2], Arunkumar et al [3] and Sacramento et al [4] showed that the reduction of the solid area in waffle flat slabs can reduce their ultimate strength, leading to the punching shear cone extending beyond the solid area. There is a rule of thumb among designers to use the length of the solid area to be at least equal to 15% of the clear span between columns, but there is no scientific basis for this rule.…”
Section: Justificationmentioning
confidence: 99%
“…Al-Bayati et al [1], [2], Arunkumar et al [3] and Sacramento et al [4] observed that some tested waffle slabs had their strength reduced when the punching shear cone reached the ribbed region. That is, in order to avoid a bearing capacity reduction of the slab, it is of fundamental importance that the punching shear cone is located within the solid area of the slab.…”
Section: Introductionmentioning
confidence: 99%
“…Ribbed and waffle slab types have many advantages. Due to the presence of voids in these slabs, the dead weight will decrease; consequently, the concrete below the neutral axis will also decrease [17]. Yet, both of these slab types have disadvantages when employed in seismic areas since they exhibit low rigidity and ductility [18].…”
Section: Introductionmentioning
confidence: 99%